L’augment verbal romanç -ez-/-iz-: derivació vs. flexió - Blaylock, Curtis (Caplletra. Revista Internacional de Filologia, 1996)
Ancient Greek could form denominal verbs by attaching a palatal semivowel to the noun stem and adding the verbal endings, thus creating verbs in -izo, -azo [això, clar, en caracters grecs], etc. Latin borrowed large enough numbers of those with vocalism in -i- so that an independently productive derivational pattern arose in Latin. As with the case of the native Latin -sk- affix, the -iz-/-ez- element developed a flexional role in some varieties of Romance. The derivational function, however, remained dominant and was even propagated to the Germanic languages.